The Used of E-Dictionary as A Media to Enhance the Students' Vocabulary - Ulandari; Paturusi, M. Arief; Junaid (Journal of Computer Interaction in Education, 2019)
This thesis aims to find out whether or not the E-Dictionary is effective in enhancing the students’ vocabulary mastery of VII A class of SMP Negeri 3 Bajeng.This research was a pre-experimental design that used pre-test and post-test. The population of this research is the VII grade students of SMP Negeri 3 Bajeng and to take the sample researcher used random cluster sampling. The research sample was 30 students. The research instrument was a vocabulary test consisting of 10 items of multiple choice.The result of the data shows that there was a difference between pre-test and post-test students. The main score of students before giving the treatment was 45 and it improved to 75.33 after applying the E-Dictionary. In addition, from t-test analysis, it was obtained that the t-test value was greater than t-table, and students’ vocabulary mastery in total (14.37>2.045). The hypothesis of this research can be concluded that Null Hypothesis (H0) is rejected and the Alternative Hypothesis (H1) is accepted. It means that E-Dictionary was effective to enhance the students’ vocabulary.